Extension of the scope of exemplary microwave power meter - Martynenko, L.G.; Komarova, A.L. (Radiotekhnika, 2017)
Using ferrіmagnetic material as an electromagnetic transducer in mechanical energy and magnetic resonance phenomena yielded sufficient mechanical energy to rotate the harness ponderomotive wattmeter fixed at both ends by means of extensions or cores. At resonance, the moment of force is (6 ± 0,5)∙10-8 N m, which is 6∙103 times more in comparison with the moment of forces achieved in the well-known works. High-precision microwave wattmeter with sufficient mechanical strength and reliability for industrial applications have been developed. The random error in the power measurement is 0.1%.